Simple biliary cysts of the liver can be lined by mucinous epithelium. Issue 3 (14th July 2022) - Wong, Newton A C S; Abdalkoddus, Muhammad; Al‐Khafaji, Nadeem; Roach, Huw; Abbadi, Reyad
Abstract : Aims & Methods: Simple biliary cysts of the liver are described to be lined by biliary epithelium and may be managed nonsurgically or by deroofing only. By contrast, its important differential diagnosis—mucinous cystic neoplasm (MCN)—is at least focally lined by mucinous epithelium, has malignant potential, and therefore should be resected. Following anecdotal observations in routine diagnostic practice, the following case series was assembled to confirm whether simple biliary cysts of the liver can be lined by mucinous epithelium. Detailed clinicoradiological review, including postoperative follow‐up, was also completed to assess whether the presence of mucinous epithelium had any associations, including a risk of hepatobiliary neoplasia. Results: Histological review of 21 simple biliary cysts received as surgical specimens over a 3‐ year period confirmed an absence of ovarian‐like stroma in all cases. The lining epithelium of seven cysts showed focal supranuclear/apical mucin, as confirmed histochemically. Cysts with mucinous epithelium were generally larger and more often showed histological evidence of previous haemorrhage than cysts without this epithelium. There were no other statistically‐significant differences in clinicoradiological features between cysts with and without mucinous epithelium, including at postoperative radiological follow‐up. Conclusions: Focal mucinous epithelium can be present in at least one‐third of surgically‐managed, simple biliary cysts of the liver. Such epithelium may be metaplastic and should not be misinterpreted to indicate a diagnosis of MCN but, apart from this, appears to have no clinical significance. Ovarian‐like stroma may therefore be the only histological feature that reliably distinguishes MCN from simple biliary cyst.